2018
DOI: 10.1016/j.watres.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partially saturated conditions on the metabolically active microbiome and on nitrogen removal in vertical subsurface flow constructed wetlands

Abstract: Nitrogen dynamics and its association to metabolically active microbial populations were assessed in two vertical subsurface vertical flow (VF) wetlands treating urban wastewater. These VF wetlands were operated in parallel with unsaturated (UVF) and partially saturated (SVF) configurations. The SVF wetland exhibited almost 2-fold higher total nitrogen removal rate (5 g TN m d) in relation to the UVF wetland (3 g TN m d), as well as a low NO-N accumulation (1 mg L vs. 26 mg L in SVF and UVF wetland effluents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 54 publications
6
18
2
3
Order By: Relevance
“…Consequently, BOD 5 removals were very high, without statistical difference between the PS VF wetlands (p > 0.05), with 91.9% and 92.2% for SI and SII, respectively. Such efficiencies are similar to those reported by [30] (higher than 90%) in a comparative study of PS VF wetlands with four different heights (5,30,45 and 60 cm) of the SZ fed with digested wastewater (resulting in a low BOD 5 /TN) and four corresponding different heights of FDZ (75, 50, 35 and 20 cm), without the addition of a SCS and using oyster shell as filter medium. However, in that study, the BOD 5 concentration in the influent was much higher (230.59 ± 92.57) mg/L than the value in this research, so future research could be conducted to assess the behavior of our systems with higher concentration of BOD 5 .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Consequently, BOD 5 removals were very high, without statistical difference between the PS VF wetlands (p > 0.05), with 91.9% and 92.2% for SI and SII, respectively. Such efficiencies are similar to those reported by [30] (higher than 90%) in a comparative study of PS VF wetlands with four different heights (5,30,45 and 60 cm) of the SZ fed with digested wastewater (resulting in a low BOD 5 /TN) and four corresponding different heights of FDZ (75, 50, 35 and 20 cm), without the addition of a SCS and using oyster shell as filter medium. However, in that study, the BOD 5 concentration in the influent was much higher (230.59 ± 92.57) mg/L than the value in this research, so future research could be conducted to assess the behavior of our systems with higher concentration of BOD 5 .…”
Section: Resultssupporting
confidence: 87%
“…Such efficiencies were much higher than the average 62% obtained by [26] in similar PS VF wetlands with the corncob in the SZ; and also higher than the 67% obtained by [22] in a PS VF wetlands with a saturation height of 35 cm planted with Phragmites australis and treating urban wastewater without the addition of an external source of carbon. In addition, [5] reported a lower TSS efficiency (74.3%) in comparison to that obtained in this study, in a pilot-scale PS VF wetland with a similar height of the SZ (35 cm) and without the addition of a solid carbon source. These findings demonstrate that the aerobic conditions in the FDZ diminished the release of suspended solids from the corncob, preventing an increase in the concentrations of TSS in the effluents.…”
Section: Tsscontrasting
confidence: 77%
See 1 more Smart Citation
“…Nitrobacter was the dominant NOB in the system because the low NO 2 − -N concentration at the inflow provided a selective advantage for Nitrobacter. This finding, which was similar to that reported in previous studies [6,37], revealed that Nitrobacter was the dominant NOB in activated sludge treated with high-N wastewater. Furthermore, in this CFM-DAS system from April to September, AOA and AOB were more sensitive to temperature than NOB.…”
Section: The Biological Oxidation Of Nhsupporting
confidence: 92%
“…In environmental microbiology it is an invaluable approach to further link microbial activity, via gene expression, to microbial and ecosystem processes, compared to DNA approaches alone (Smith and Osborn, ; Saleh‐Lakha et al ., ; Gadkar and Filion, ). As a result the approach has been used to quantify transcripts to distinguish different pathways of the nitrogen cycle in sediments (Smith et al ., ; Santoro et al ., ; Zheng et al ., ; Damashek et al ., ; Duff et al ., ; Santos et al ., ; Zhang et al ., ), soil (Leininger et al ., ; Graham et al ., ; Wang et al ., ; Li et al ., ; Pierre et al ., ), water column (Santoro et al ., ; Kapoor et al ., ; Tolar et al ., ; Posman et al ., ; Feng et al ., ; Gonçalves et al ., ; Liu et al ., ; Christiansen et al ., ) and other microbial processes including water treatment (Botes et al ., ; Gadkar and Filion, ; Wang et al ., ; Pelissari et al ., , ) and bioremediation (Yergeau et al ., ; Marzorati et al ., 2010; Gadkar and Filion, ). In addition to this, cDNA from mRNA or rRNA can undergo PCR for amplicon sequencing to reveal actively transcribing organisms within the environment (Duff et al ., ; Zhang et al ., ; Cholet et al ., ).…”
Section: Introductionmentioning
confidence: 99%